2020
DOI: 10.1002/art.41190
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Resistant Pathways Are Associated With Disease Activity in Rheumatoid Arthritis and Are Subject to Disease Modification Through Metabolic Reprogramming: A Potential Novel Therapeutic Approach

Abstract: Objective. To investigate a role for insulin-resistant pathways in inflammation and therapeutic targeting for disease modification in rheumatoid arthritis (RA).Methods. RA disease activity and cardiovascular risk factors, including insulin resistance and body mass index (BMI), were assessed in an Irish RA cohort. Glucose transporter 1 (GLUT-1) and GLUT-4 activity in RA and osteoarthritis (OA) synovial tissue was examined using immunohistochemistry. Spontaneous release of proinflammatory mediators from ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…We have also demonstrated that the cells remain viable in culture and spontaneously secrete proinflammatory cytokines [25,26]. Furthermore, we have demonstrated that the explant model can be utilized to examine the effect of therapeutic targets, including tofacitinib, metformin and OPN301 [21,22,27,28]. Collectively, this suggests that the synovial explant ECM used throughout this study is a good model to reflect the joint microenvironment.…”
Section: Resultsmentioning
confidence: 97%
“…We have also demonstrated that the cells remain viable in culture and spontaneously secrete proinflammatory cytokines [25,26]. Furthermore, we have demonstrated that the explant model can be utilized to examine the effect of therapeutic targets, including tofacitinib, metformin and OPN301 [21,22,27,28]. Collectively, this suggests that the synovial explant ECM used throughout this study is a good model to reflect the joint microenvironment.…”
Section: Resultsmentioning
confidence: 97%
“…Increased IR, estimated by the homeostatic assessment model (HOMA-IR), has been reported in RA patients compared with healthy controls [18][19][20][21][22], but the cause is still unclear. Some RA studies revealed a significant correlation of HOMA-IR with markers of inflammation [22][23][24], which was not the case in other investigations [18][19][20][21]25]. Similarly, divergent results exist regarding RA activity.…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, divergent results exist regarding RA activity. Several authors demonstrated a significant correlation between disease activity score of 28 joints (DAS28) and HOMA-IR [22][23][24][25], while others did not [18][19][20][21]. Furthermore, impaired β-cell function was also shown in several RA studies [18,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Lower increase in Th17 cells with reduction of proinflammatory cytokines and improved arthritis score in a CAIA mouse model [20,21] Suppression of Th17 cells and enhancement of Treg cells in a CIA murine model [22] Suppression of osteoclast differentiation [23] Impaired autophagy correction with suppression of inflammatory cytokines and clinical arthritis in a murine model of immune arthritis [24] Higher reduction of Th17 cells, induction of Treg cells, and inhibition of osteoclastogenesis with higher arthritis improvement by metformin combined with CoQ10 vs. metformin or CoQ10 alone in a CIA murine model [25] Restoration of reciprocal Th17/Treg balance with dampened CIA development in a murine model of diet-induced obesity [26] Modulation of macrophage polarization toward M2 phenotype in a model of high-fat diet-fed obese C57/6J male mice [27] Inhibition of RA-FLS proliferation on synovial tissue from patients with RA [28] Mitochondrial dysfunction reduction by rapamycin combined with metformin vs. rapamycin alone in a CIA obese mouse model [29] Reduction of GLUT-1 expression in synovial tissue from patients with RA [30] Inverse association between risk of RA and exposure to metformin inT2DM patients [31] Lower admission rate of T2DM patients with RA treated with metformin and Cyclooxygenase (COX)-2 inhibitor vs. COX-2 inhibitors alone [32] Osteoarthritis (OA)…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Based on previous studies reporting an increased prevalence of altered glucose metabolism in RA patients [68,69], the relationship between insulin resistance and disease activity was recently further explored in an Irish cohort of 92 patients with RA [30]. Using ex vivo synovial explants from RA patients and osteoarthritis (OA) non-inflammatory controls, the activity of glucose transporters GLUT1 (largely insulin-dependent) and GLUT4 (activated under the influence of insulin) was measured.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%